Appreciation of Authenticity Promotes Curiosity: Implications for Object-based Learning in Museums. (2nd July 2016) - Bunce, Louise
ABSTRACT: Museum professionals suppose that interacting with authentic objects promotes curiosity and engagement, but this has not been tested. In this research, children and adults visiting the Oxford University Museum of Natural History were shown a taxidermied rabbit or rabbit skeleton. They were asked "Is it real?", "Why?" and were given the opportunity to ask a question about it to measure their curiosity and engagement. As predicted, visitors who perceived the rabbits as authentic were more likely to ask a question than those who judged them as inauthentic. Perceived authenticity also promoted more why questions. In general, these findings became more robust with increasing age. However, approximately 25% of visitors did not perceive the rabbits as authentic. This study thus supports the assumption that authentic objects are associated with increased curiosity and engagement but museum professionals need to ensure that visitors know when they are interacting with the real thing.